Challenging Malawian primary teachers' views on mathematics teaching and learning through lesson study. Issue 1 (11th January 2022) - Fauskanger, Janne; Helgevold, Nina; Kazima, Mercy; Jakobsen, Arne
Abstract : Purpose: The aim of the study is to better understand how lesson study (LS) contributes to challenging teachers' views of mathematics teaching and learning. Design/methodology/approach: This study is part of a wider ongoing project aiming at improving primary mathematics teaching in Malawi through professional development (PD) of teachers using a LS model. The units being analyzed are teachers' written reflections and lesson plans. The analytical approach is qualitative content analysis. Findings: Initially, the participating Malawian primary teachers report traditional views of mathematics teaching and learning. After having participated in a LS cycle, they reported on the need to work on how to involve and create space for learners' participation in mathematic lessons and highlight the importance for learners to discover mathematics on their own. Research limitations/implications: This is a small-scale study due to LS being quite new in the Malawian context and the need to test before possible upscaling. Practical implications: The paper includes a description on how LS might contribute to challenging Malawian teachers' views of mathematics teaching and learning; this can be valuable information for others who are attempting to use LS in a similar context. Originality/value: This paper fulfills an identified need to learn more about how LS might contribute to challenging teachers' views of mathematics teaching and learning worldwide.